2019
DOI: 10.3390/nu11091963
|View full text |Cite
|
Sign up to set email alerts
|

The Postprandial Appearance of Features of Cardiometabolic Risk: Acute Induction and Prevention by Nutrients and Other Dietary Substances

Abstract: The purpose of this review is to provide an overview of diets, food, and food components that affect postprandial inflammation, endothelial function, and oxidative stress, which are related to cardiometabolic risk. A high-energy meal, rich in saturated fat and sugars, induces the transient appearance of a series of metabolic, signaling and physiological dysregulations or dysfunctions, including oxidative stress, low-grade inflammation, and endothelial dysfunction, which are directly related to the amplitude of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 214 publications
(267 reference statements)
1
30
1
Order By: Relevance
“…Moreover, differences could have been caused by different effects on inflammation. However, two meta-analyses showed that longer-term consumption of tree nuts [57] and L-arginine supplementation [58] did not affect fasting inflammation, whereas positive effects of tree nut consumption on postprandial markers of inflammation and oxidative stress has been reported [59]. However, L-arginine supplementation did not affect postprandial inflammation [35], which might be due to the short half-life of L-arginine of about 90 min [60].…”
Section: Table 2amentioning
confidence: 97%
“…Moreover, differences could have been caused by different effects on inflammation. However, two meta-analyses showed that longer-term consumption of tree nuts [57] and L-arginine supplementation [58] did not affect fasting inflammation, whereas positive effects of tree nut consumption on postprandial markers of inflammation and oxidative stress has been reported [59]. However, L-arginine supplementation did not affect postprandial inflammation [35], which might be due to the short half-life of L-arginine of about 90 min [60].…”
Section: Table 2amentioning
confidence: 97%
“…Postprandial hyperglycemia and hyperlipidemia exacerbate postprandial systemic inflammation and vasoconstriction. The degree of response can be assessed by measuring select inflammatory biomarkers and nitrite that are sensitive to dietary challenges [ 55 ]. In randomized controlled clinical trials, acute interventions with dietary polyphenols have shown promise in mitigating postprandial inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The release of fatty acids from solid food was lower than that from liquid or semisolid food, and the postprandial TG elevation caused by solid food was lower than that of liquid food ( 101 ). A range of metabolic, physiological, or functional disorders may occur transiently after ingestion of a high-energy diet rich in fat, and the process is strongly associated with postprandial TG ( 102 ). Postprandial CM-TG response increased with an increase in dietary fat content in normal weight and obese individuals ( 79 ).…”
Section: Interventions On Postprandial Lipemiamentioning
confidence: 99%